Education in the New Millennium: The Case for Design-Based Learning. - Lee, Hyun-Kyung; Breitenberg, Mark (International Journal of Art & Design Education, 2010)
This article focuses on current examples of project or design-based learning at the secondary school level in the context of the increasing importance of creativity and innovative thinking in the twenty-first century. The authors argue that students today learn more effectively in pedagogical practices that emphasise holistic thinking, active learning, visual media and problem-solving. Design-based learning presents new ways for realising long-term goals and learning outcomes. The purpose of this article is to investigate best practices of design education in the community and to propose instructional resource examples on design to K-12 school teachers. This article points out the importance of systemised process for the work of design-based teachers and learners, addresses the study of design as a subject of investigation and a mode of inquiry that engages a variety of student learning styles and makes direct connections between subjects and problem-solving in daily life. Our belief is that the case studies explored in this article represent the seeds of a new model of education based on creative and applied learning. The exemplar communities chosen for onsite research are the education department of the Cooper-Hewitt National Design Museum in New York City and the Art Center College of Design in Pasadena, California, USA.